1993
DOI: 10.2135/cropsci1993.0011183x003300020024x
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Sample Preparation for HPLC Analysis of Ergovaline in Tall Fescue

Abstract: Increased interest in the endophytic fungus, Acremonium coenophialum Morgan‐Jones & Gams, and its symbiotic inhabitance of tall fescue, Festuca arundinacea Schreb., has created the need for rapid and reliable ergovaline analysis in research and in extension service (for diagnosis). A simplified sample preparation method provides faster and more reproducible results for ergovaline quanitation in tall fescue. The method involves extraction with alkaline chloroform, purification with a silica gel solid‐phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…All samples were freeze‐dried and ground through a 1‐mm screen using a cyclone‐type mill. Ground samples were analyzed for ergovaline by HPLC according to the procedure of Rottinghaus et al (19) with modifications reported by Hill et al (8). Samples were also analyzed for total ergot alkaloids by enzyme‐linked immunosorbent assay (ELISA) according to the procedure of Hill and Agee (7) with a commercial test kit from Agrinostics, Ltd. (Watkinsville, GA).…”
Section: Laboratory Analysismentioning
confidence: 99%
“…All samples were freeze‐dried and ground through a 1‐mm screen using a cyclone‐type mill. Ground samples were analyzed for ergovaline by HPLC according to the procedure of Rottinghaus et al (19) with modifications reported by Hill et al (8). Samples were also analyzed for total ergot alkaloids by enzyme‐linked immunosorbent assay (ELISA) according to the procedure of Hill and Agee (7) with a commercial test kit from Agrinostics, Ltd. (Watkinsville, GA).…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Heifers were weighed on d 56 (midpoint) and 99 (termination of grazing) in yr 1, and on d 60 (midpoint) and 116 (termination of grazing) during yr 2. To assess toxicity of fescue pastures, random forage samples (8 to 10 samples per ha) were collected monthly from each pasture, pooled within pasture, cut into 5.1-cm pieces, and stored at −4°C until ergovaline concentrations were determined using high-performance liquid chromatography [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Ergovaline concentration was determined by high-pressure liquid chromatography (HPLC) using the procedure reported by Rottinghaus et al (1991) with modifications reported by Hill et al (1993). Ten plots from the remaining grazing events were randomly chosen, giving a total of 74 samples for ergovaline determination.…”
Section: Initial Gps Data Determinationmentioning
confidence: 99%